Association of distinct microbial and metabolic signatures with microscopic colitis - Chen, Albert Sheng-Yin; Kim, Hanseul; Nzabarushimana, Etienne; Shen, Jiaxian; Williams, Katherine; Gurung, Jenny; McGoldrick, Jessica; Burke, Kristin E.; Yarze, Joseph C.; Nguyen, Long H.; Staller, Kyle; Chung, Daniel C.; et al. (NATURE COMMUNICATIONS, 2025)
Microscopic colitis (MC) is a chronic inflammatory disease of the large intestine that primarily affects older adults and presents with chronic diarrhea. The etiology is unknown and there are currently no FDA approved medications or biomarkers for treatment or monitoring of the disease. Emerging evidence have implicated the gut microbiome and metabolome disturbances in MC pathogenesis. We conduct a comprehensive analysis of gut microbial and metabolic changes in a cohort of 683 participants, including 131 patients with active MC, 159 with chronic diarrhea, and 393 age- and sex-matched controls without diarrhea. Stool microbiome and metabolome are profiled using whole-genome shotgun metagenomic sequencing and ultra-high performance liquid chromatography–mass spectrometry, respectively. Compared to controls, eight microbial species including pro-inflammatory oral-typical Veillonella dispar and Haemophilus parainfluenzae , and 11 species, including anti-inflammatory Blautia glucerasea and Bacteroides stercoris are enriched and depleted in MC, respectively. Pro-inflammatory metabolites, including lactosylceramides, ceramides, lysophospholipids, and lysoplasmalogens, are enriched in active MC. Multi-omics analyses reveal robust associations between microbial species, metabolic pathways, and metabolites, suggesting concordant disruptions in MC. Here, we show distinct shifts in gut microbiome and metabolome in MC that can inform the development of non-invasive biomarkers and novel therapeutics. Here, the authors identify distinct gut microbiome and metabolome signatures in microscopic colitis, a condition causing chronic diarrhea, highlighting pro-inflammatory species and metabolites as potential non-invasive biomarkers and therapeutic targets.